An Environment for Exploring Generalized Association Rules - Domingues, Marcos A.; Figueiredo, Matheus G. B.; Rezende, Solange O. (Proceedings of the National Meeting on Artificial and Computational Intelligence (ENIAC), 2007)
The Data Mining (DM) process enables that end users can analyse, understand and use the extracted knowledge in an intelligent system or to support decision processes. However, many algorithms used in the process find large quantities of patterns, complicating the analysis of the patterns. This fact occurs with Association Rules (AR), a technique that tries to identify intrinsic patterns in large data sets. A method that can help the analysis of the rules is the generalization of the AR. In this paper, we propose an environment to generalize AR and to analyse the generalized rules.